2020
DOI: 10.1007/s00223-020-00720-4
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin and Liraglutide Therapies Rapidly Enhanced Bone Material Properties and Matrix Biomechanics at Bone Formation Site in a Type 2 Diabetic Mouse Model

Abstract: Aim: To compare head-to-head the effects of dapagliflozin and liraglutide on bone strength and bone material properties in a pre-clinical model of diabetes-obesity. Materials and methods: Combined low-dose streptozotocin and high fat feeding were employed in mice to promote obesity, insulin resistance and hyperglycaemia. Mice were administered daily for 28 days with saline vehicle, 1mg/kg dapagliflozin or 25 nmol/kg liraglutide. Bone strength was assessed by three-point bending and nanoindentation. Bone materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Right femurs were embedded undecalcified in pMMA after dehydration and infiltration, as previously reported [ 35 ]. One micrometre-thick sections of the midshaft femur were cut with an ultramicrotome (Leica EM UC7, Leica microsystems, Nanterre, France) and deposited on BaF2 windows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Right femurs were embedded undecalcified in pMMA after dehydration and infiltration, as previously reported [ 35 ]. One micrometre-thick sections of the midshaft femur were cut with an ultramicrotome (Leica EM UC7, Leica microsystems, Nanterre, France) and deposited on BaF2 windows.…”
Section: Methodsmentioning
confidence: 99%
“…The contribution of pMMA at ~1730 cm −1 was computed and a nanoporosity ratio (area ratio 1730 cm −1 /v1,v3 PO4) was calculated. After pMMA subtraction, the spectrum was vector-normalized for the v1, v3 phosphate band and analysed with a routine script in Matlab R2021b (The Mathworks, Natick, MA, USA), as previously reported [ 35 ]. Phosphate/amide I ratio (area of v1,v3 phosphate/area amide I), mineral crystallinity (1/full width at half-maximum of the v1 PO 4 peak at 960 cm −1 ), crystal size index (area ratio: ~1076 cm −1 /~1058 cm −1 ), acid phosphate content (area ratio: ~1127 cm −1 /~1096 cm −1 ), carbonate/phosphate ratio (intensity of v2 carbonate located at 850–900 cm −1 /v1,v3 PO4 band) and collagen maturity (area ratio: ~1660 cm −1 /1690 cm −1 ) were computed.…”
Section: Methodsmentioning
confidence: 99%
“…In patients receiving metformin-based background therapy who have an increased cardiovascular risk, specific GLP-1RAs and SGLT-2is have demonstrated favourable effects on certain cardiovascular outcomes [ 40 ]. However, studies have also shown that the effects of dapagliflozin and liraglutide on bone material properties are not identical and are not only mediated by low blood glucose levels [ 41 ]. Therefore, other effects of these two new hypoglycaemic drugs need to be confirmed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Post-processing was performed with a lab-made Matlab routine (R2020b, The Mathworks, Natick, CA) and included Mie scattering correction, second-derivative spectroscopy, and curve fitting routines. Trivalent collagen crosslink content (Area ratio 1660 cm -1 /Amide 1), divalent collagen crosslink content (Area ratio 1690 cm -1 /Amide 1), and collagen maturity (area ratio 1660/1690 cm -1 ) were computed as reported previously ( 23 ).…”
Section: Methodsmentioning
confidence: 99%